Persistent organic pollutants and mortality in the United States, NHANES 1999-2011 - Kristiann Fry; Melinda C. Power (BMC, 2017)
Abstract Background Persistent organic pollutants (POPs) are environmentally and biologically persistent chemicals that include polybrominated diphenyl ethers (PBDEs), per- and polyfluoroalkyl substances (PFASs), polychlorinated biphenyls (PCBs), and organochlorine (OC) pesticides. Currently, data on the associations between exposure to POPs and the risk of mortality in the U.S. population is limited. Our objective was to determine if higher exposure to POPs is associated with greater risk of all-cause, cancer, heart/cerebrovascular disease, or other-cause mortality. Methods Analyses included participants aged 60 years and older from the 1999-2006 National Health and Nutrition Examination Surveys (NHANES). We included 483 participants for analyses of PBDEs, 1043 for PFASs, and 461 for PCBs, and 1428 for OC pesticides. Exposures to POPs were estimated using biomarkers measured in serum. Mortality status through December 31, 2011 was obtained from public-use, linked mortality files. We used Cox proportional hazard models to quantify the associations of interest. Where we observed an association, we explored effect modification by sex, body mass index, smoking status, and albuminuria. We also explored the combined effect of PBDEs and OC pesticides in the subsample of participants with measures of both analytes. Results Serum measurements of PBDEs, PFASs, and PCBs were not clearly associated with increased all-cause or cause-specific mortality in older Americans. Beta-hexachlorocyclohexane was associated with an increased risk of all-cause mortality [HR per 1 SD increase =1.18, 95% CI = 1.01, 1.38]. Oxychlordane [HR = 1.15 95% CI 1.06, 1.25], p,p'-DDE [HR = 1.12, 95% CI = 1.02, 1.23], trans-nonachlor [HR = 1.11, 95% CI = 1.04, 1.18], and beta-hexachlorocyclohexane [HR = 1.25, 95% CI = 1.03, 1.52] were associated with increased risk of other-cause mortality. Exploratory analyses suggested associations between OC pesticides and other-cause mortality were modified by sex. Exploratory analyses also suggested that the combination of high PBDE and high OC pesticide exposure had a stronger than expected adverse effect on all-cause mortality. Conclusion Higher exposure to beta-hexachlorocyclohexane, an OC pesticide, is associated with increased all-cause mortality and higher exposure to four OC pesticides is associated with increased non-cancer, non-heart/cerebrovascular disease mortality in U.S. adults 60 years or older. These associations may be modified by sex or exposure to other POPs.